Institutional Quality and Fiscal Transparency - Nicolo Andreula; Alberto Chong; Jorge Guillen (Inter-American Development Bank (IDB), 2009)
This paper uses new data on fiscal transparency for a cross-section of countries; these data possess several advantages. First, the data are based on in-depth reports using a standardized methodology and protocol. Second, this study covers 82 countries, more than previous comparable studies. Third, the fiscal measures used have been obtained with the collaboration of government authorities, which makes them particularly reliable. Finally, the data collection has been undertaken at a high level. These new data permit examination of a relevant but little-studied issue, the role of institutional quality in a countrys fiscal transparency. It is shown that there is in fact a causal relationship between institutions and transparency. The findings are robust to changes in specification and a host of transparency sub-measures.
Keywords: H50; H83; 330; Fiscal management; Institutions; Public administration; Transparency